EU – 30 Years After Maastricht – The Polish Perspective – From Hope to Disillusionment - Bryk, Andrzej (Maastricht 30: A Central European Perspective, 2025)
After the reunification of Germany, the Maastricht Treaty and the Treaty of Lisbon, the European Union underwent a radical transformation on an axiological, political and systemic level. It has become a messianic project of integration, led by oligarchic elites. The ideology of this legal and political process is a monistic emancipatory liberalism, formed under the influence of a Western European left sympathetic to Marxism and Soviet communism. Its aim is the supposed abolition of oppression and all discriminationwith the help of EU Court of Justice jurisprudence and legislation. In reality, the technocrats who run the EU, seek to dismantle the rootedness of citizens of East-Central European nation states in the family, in religions and traditional values. EU legislation, especially the Charter of Fundamental Rights, which is essentially an ideological manifesto, must be viewed and interpreted in this context.Non-liberal values are regarded by the EU establishment as a source of discrimination and oppression of individuals. Only liberal emancipation from any relationship and community that is not based on completely free, autonomous choice is to guarantee the freedom and happiness of citizens of a new European-wide empire led by Germany.The plan to build such a total empire with Germany at its head threatens the independence of the post-communist countries of Central Europe, including Poland. It is also reminiscent of the epoch of Soviet dominance. Neo-colonial cooperation between local post-communist elites and centers of power in Brussels and Berlin is also important. A significant proportion of citizens, disillusioned by the imitative modernization and post-1989 economic policies, are turning to parties offering alternative. Elites deprecate this phenomenon by referring to it with the pejorative term “populism”, thus attempting to disqualify their opponents as enemies of human rights, of the rule of law and of the so-called “European values”.Keywords: Poland after 1989, emancipatory liberalism, German neo-imperialism, liberal vision of European integration, technocracy, ‘democratic deficit’ in the EU, European populism